Spatial Analysis Risk Factors of Pneumonia Incidence in Toddlers Gowa Regency - Z. Monoarfa, Melani Zulhidayati; Maria, Ida Leida; Ansariadi, Ansariadi; Arsin, A. Arsunan; Amqam, Hasnawati (International Journal of Statistics in Medical Research, 2025)
Background: Pneumonia is one of the highest causes of death in children under five years old in the world. Globally, the number of under-five deaths due to pneumonia is estimated to reach up to 700,000 cases per year. Objectives: This study aimed to spatially analyze the risk factors for pneumonia incidence among under-fives in Gowa Regency in 2021-2023. Methods: This study used an analytic observational with an ecological study design. The population in this study was all cases of pneumonia among under-fives in Gowa Regency in 2021-2023, totaling 1,634 cases. The sample size in this study was 18 subdistricts with the sample selection technique using the exhaustive sampling method. Results: There was a relationship between population density (r=0.470 p=0.000), poor population (r=0.422 p=0.001) and incomplete immunization status (r=0.457 p=0.000) with the incidence of pneumonia among under-fives in Gowa Regency in 2021-2023. Meanwhile, there was no association between undernutrition status (r=0.250 p=0.068) with the incidence of pneumonia among under-fives in Gowa Regency in 2021-2023. Conclusion: Although undernutrition status did not show a statistically significant association in this study, it remains an important risk factor in the susceptibility of under-fives to pneumonia and other infections. Children with undernutrition status have a weak immune system, making them susceptible to disease complications. Therefore, nutritional interventions such as the provision of supplementary food, increasing exclusive breastfeeding coverage, and nutrition education to parents still need to be developed in a sustainable manner.